KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK DITINJAU DARI GAYA KOGNITIF FIELD INDEPENDENT DAN FIELD DEPENDENT - Lestari, Silva Dwi; Sumarni, Sumarni; Riyadi, Mohamad (Pendidikan Matematika UNIMOR, 2022)
The purpose of this study is to analyze the mathematical problem-solving ability of SMK students with cognitive style Field Independent (FI) and Field Dependent (FD). The type of research is qualitative research with descriptive method. The research subjects are 23 students of class X SMK who had studied the Linear Programming material and four people were taken for analysis, namely two FI students and two FD students. Subjects are taken using a purposive sampling technique. This research instrument uses the Group Embedded Figures Test (GEFT), tests of mathematical problem-solving ability and interview guidelines. The results showed that the first FI subject who had a very good problem-solving ability category met all the indicators of problem-solving ability. The second FI subject who has a good problem-solving ability category meets three indicators of problem-solving ability. The first FD subject who has sufficient problem-solving ability category cannot fulfill all problem-solving indicators. The second FD subject who has a problem-solving ability category is sufficient to meet two indicators of problem-solving ability. It can be concluded that the problem solving ability of SMK students is quite good.